Implications of root morphology and anatomy for water deficit tolerance and recovery of grapevine rootstocks - Alonso-Forn, David; Buesa, Ignacio; Flor, Luis; Sabater, Antoni; Medrano, Hipólito; Escalona, José M. (Frontiers in Plant Science, 2025)
The intensification of drought conditions due to climate change poses a major challenge to sustainable grape production. Rootstocks are essential in supporting grapevine water uptake and drought resilience; however, their physiological responses to water stress are not fully understood. Under the hypothesis that root morphology and anatomy may be key traits in grapevine tolerance to water deficit, this study aimed to investigate these traits across diverse rootstocks under progressive water deficit and recovery phases. Thirteen genotypes, including commercial rootstocks and recently bred RG-series and RM2, were evaluated over two seasons in controlled pot-based conditions. Plants were subjected to five distinct watering stages, from well-watered to severe drought. Root traits, such as length, density, and xylem anatomical features, were analyzed alongside stem water potential (Ψstem) to gauge plant water status. Results showed significant genotype-specific differences in root morphology and anatomy, impacting drought tolerance and recovery. Rootstocks with higher root length density (RLD) and a larger proportion of fine roots maintained Ψstem more effectively under severe drought. Additionally, smaller xylem vessel diameters and reduced xylem area relative to root cross-sectional area correlated with improved water transport efficiency and faster recovery post-drought. A trade-off emerged wherein increased root density enhanced water uptake capacity but came at the cost of reduced transport efficiency. Notably, rootstocks 420A, 41B, RM2, and Fercal displayed superior drought resilience, while the RG-series did not outperform established genotypes like 13-5 Evex, 110 Richter, and 140 Ruggeri. These results underscore the role of root morphology and anatomy in grapevine drought tolerance, suggesting that these traits could be incorporated as criteria for future rootstocks breeding programs. Nevertheless, field-testing under non-limiting soil conditions is essential to validate these findings.